2018
DOI: 10.1525/irqr.2018.11.3.334
|View full text |Cite
|
Sign up to set email alerts
|

Designing for Discomfort

Abstract: In this article we explore discomforts two doctoral students experienced in a qualitative research methods class designed to introduce the diversity of qualitative research. The discomforts, purposefully facilitated by the teacher, created opportunities for students to consider their roles as professionals and scholars. We use student class posts, reflection journals, and audio-recorded conversations from our yearlong research to focus on the discomfort of nonsingularity of qualitative research. We make visibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Sometimes being knowledgeable about data collection methods, theory, tips, and challenges may not prevent researchers from facing unanticipated challenges during the data collection (Rimando et al, 2015); this is a situation reflecting the non-linearity of qualitative research. The vulnerability of not knowing qualitative research in certain terms can lead students to understand qualitative research deeply (Skukauskaite, Noske, & Gonzales, 2018). Due to the variety and possibilities of qualitative data analysis, it can be daunting for novice researchers to choose the right combination of research methodologies, data collection instruments, and analysis methods (Kalpokaite & Radivojevic, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sometimes being knowledgeable about data collection methods, theory, tips, and challenges may not prevent researchers from facing unanticipated challenges during the data collection (Rimando et al, 2015); this is a situation reflecting the non-linearity of qualitative research. The vulnerability of not knowing qualitative research in certain terms can lead students to understand qualitative research deeply (Skukauskaite, Noske, & Gonzales, 2018). Due to the variety and possibilities of qualitative data analysis, it can be daunting for novice researchers to choose the right combination of research methodologies, data collection instruments, and analysis methods (Kalpokaite & Radivojevic, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Through a personal narrative, Bowen (2005) reported the learned lessons during her qualitative research-based dissertation: the significance of reading, consulting the experts, adhering to university regulations, paying attention to rigor and trustworthiness, giving details of the methodology, not being afraid to include numerical data, and preparing to publish. Furthermore, Skukauskaite et al (2018) uncovered that students stated their discomfort and confusion about qualitative research by signifying the contribution of this discomfort for their development as scholars. Roulston, Preissle and Freeman (2013) found that novices developed their voices as scholars by engaging in various scholarly debates about research topics and questions during their dissertation journey.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, an initiate to learning qualitative research may be both eager and confident, but at the same time hesitant to work with images as they remain an undefined terrain. Choosing the unknown implies discomfort (Skukauskaite, Noske & Gonzales, 2018). Opting for a research method that deviates from more conventional analytical approaches can be scary.…”
mentioning
confidence: 99%